Acanthamoeba infection in an interhemispheric ependymal cyst: a case report. - Ranjan, R; Handa, A; Choudhary, A; Kumar, S (2009)
BACKGROUND: Free-living amoebae are known to cause fatal granulomatous encephalitis in immunocompromised individuals. They are also known to present as multifocal parenchymal lesions, pseudotumoral lesions, meningeal exudates, hemorrhagic infarcts, and necrosis in the brain. However, Acanthamoeba infection in an intracranial ependymal cyst has not been reported in the literature. CASE DESCRIPTION: A 25-year-old immunocompetent man presented with a suspected interhemispheric arachnoid cyst. The cyst fluid turned out be infected with Acanthamoeba. The patient was treated successfully with decompression of the cyst with combination chemotherapy. CONCLUSION: Acanthamoeba may cause secondary infection in an underlying brain cyst. A suspicion of such an infection must be raised in the presence of altered nature of CSF consistency. The aggressive chemotherapy is the only hope for favorable outcome. The dilemmas associated with the diagnosis and treatment are further discussed.